TURKEY AS A BALANCER IN THE BLACK SEA BASIN - Göktürk TÜYSÜZOĞLU (Fırat University, 2021)
Black Sea Basin is located in a zone where Europe and Asia converges proximately and couldn’t exhibit sufficient development in terms of regional identity, due to social, geographical and political differences. The region is examined under the definition of Wider Black Sea upon change of structure and scope in international system after the Cold War. The region has become a zone, where interests of the US and Russia, have fallen into conflict at the post-millennium era. Black Sea Region is important both for the eastern opening of the EU and NATO and for the energy policies of EU, Russia, US and Turkey. Beginning to pay great attention to her newly-adopted foreign policy strategy, Turkey acts within the framework of regional advantages which she has obtained. Giving up foreign policy strategy focused only upon the membership of EU, Turkey has realized that activity around her close surrounding shall be reflected upon Turkey’s regional perception. Turkey’s approach towards the countries of the basin could be defined within the framework of theories such as soft power and mutual interdependence. Black Sea Strategy of Turkey focuses on the fact of cooperation through the sectors such as energy, transportation and trade, which reflect the economic potential of the region.